Effect of Next Generation Fertilizers on Yield Potential of Rice (Oryza sativa L.) - Faroque, M. A. A.; Paul, Alok Kumar; Asaduzzaman; Bissus, Parimal; Islam, M. S. (International Journal of Bio-resource and Stress Management, 2021)
The experiment was carried out to evaluate the effects of next-generation fertilizers along with other recommended fertilizers on the growth and yield during the period from January 2015 to May 2015 at the experimental field of Sher-e-Bangla Agricultural University, Sher-e-Bangla Nagar, Dhaka, Bangladesh. The experiments were laid out in RCBD method with three replications. The experiment was conducted in boro rice with six treatments including control viz Treatment0 = Control (no fertilizer), Treatment1 = Recommended dose N140P20K60S18Zn2 kg ha-1, Treatment2 = Bio-forge + N140P20K60S18Zn2, Treatment 3 = Wuxal Super+N140P20K60S18Zn2, Treatment4= Root feed + N140P20K60S18Zn2, Treatment5=Nitro Plus+N140P20K60S18Zn2 and three rice varieties namely Variety1 = BRRI dhan29, Variety2 = BRRI dhan28 and Variety3=BRRI dhan58. Next-genaration fertilizer is a mixed fertilizer with the first generation and second generation fertilizer that provide required nutritions to plants. Among the next generation fertilizers, Bio-forge along with other recommended fertilizers performed the best compared to other treatments of the study in an aspect of growth and yield contributing characters mainly plant height, effective tiller hill-1, panicle length, filled grain panicle-1, 1000-grain weight, harvest index and grain yield (8.61 t ha-1). Among the varieties, BRRI dhan29 showed the best performance compared to the other two treatments. The next generation fertilizer viz. Bio-forge and Root feed along with other recommended fertilizers would be ideal for better crop growth and yield.